Association Between Stress at Work and Onset of Menopause in Senior High Schools Women Teachers in Surakarta - Arditya, Canda; Riyadi, Slamet; Mashuri, Yusuf Ari (Nexus Kedokteran Komunitas, 2017)
Bacground: Stress has been already known affecting hormonal axis. However, the association between stress and menopause is poorly understood. The study was aimed to determine the association between stress at work and the onset of menopause of the women teachers in Senior High Schools in Surakarta. Methods: This was an observational cross-sectional research using cross sectional design. The sampleÂ was activeÂ womenÂ teachers who wereÂ regularlyÂ Â teaching inÂ Senior High Schools at Suraâkarta who already had menstrual periods stop.Â SamplingÂ was done using a simple random sampling method with amount of sample 58Â womenÂ teachers. The data of stress at work were obtained by International Stress Management Assosiation (ISMA) quistionare and the onset of menopause were obtained by interviews. The data were analyzed with unpairedÂ t-test and SpearmanÂ correlationÂ test. Results: Stress at workÂ  was significantly correlated with the onset of menopause (r = -0.441; p = 0.009). Stress at work was found to be significantly associated with onset of menopauseÂ  (p < 0.05). Conclusion: This research shows a significant correlation between work stress and the onset of menopause with negative direction andÂ  moderate strength. Keywords: menopause, stress at work